Prevalence and Association of Hypertension among the Government Civil Employees of Bangladesh Armed Forces Attending BNS Patenga (Navy Hospital), Chattogram (Community Based Medical Journal, 2024)
Hypertension is a major risk factor for several cardiovascular diseases (CVD). A descriptive, cross-sectional study was conducted to estimate the prevalence of hypertension and its risk factors among the government civil employees of Bangladesh Armed Forces reported to BNS Patenga (Navy Hospital), Chattogram, Bangladesh, between January and June 2023. The study involved participants aged 25-60 years who are government civil employees working in Bangladesh Armed Forces in Chattogram area. This study was done using multi-stage random sampling. Data on age, gender, smoking habits, sedentary lifestyle, obesity, diabetes, dyslipidemia, physical activity, diet, extra salt use, family history of hypertension, cardiovascular disease and cerebrovascular disease, anthropometric measurements and blood pressure were collected using modified WHO-STEPS protocol. Hypertension was defined according to JNC-8 guidelines. Multiple logistic regressions models were used to identify risk factors associated with hypertension. Data were collected with semi-structured questionnaire and checklist by face-to-face interview and reviewing medical records respectively. Data were analyzed by SPSS version 19.0. A total of 150 participated (128 male and 22 female). Among the study population, 17% had hyperlipidemia, 32% consume high caloric diet, 15% were overweight, 20% had smoking habit, 17% were working in stressful environment, 57% were sedentary worker, 19% having family history of hypertension. The overall age-adjusted prevalence hypertension among 150 participants was 27%, which was higher among males compared to females (25% in contrast to 2%). Bivariate analysis showed significant relationship of hypertension with age, BMI, no physical activity, tobacco use, extra salt intake, dyslipidaemia, stressful life, high calorie diet, diabetes, and family history of stroke/cardiovascular disease, hypertension, diabetes and dyslipidaemia. In the multivariate model, factors significantly associated with hypertension were older age (33%), smoking (26%), extra salt intake (35%), and high waist circumference (36%). The prevalence of hypertension was high among our study participants. Population-based intervention programs and policies for increased awareness about the risk factors, and life-style modification are essential for prevention of hypertension.  CBMJ 2024 January: vol. 13 no. 01 P: 17-21